Uncovering the decision‐making work of transferring dying patients home from critical care units: An integrative review. (17th July 2017) - Lin, Yanxia; Myall, Michelle; Jarrett, Nikki
Abstract: Aims: To understand how decisions are made to transfer dying patients home from critical care units. Background: Many people prefer a home death, but a high proportion die in critical care units. Transferring dying patients home is recognized to be complex but transfer decision‐making itself remains unclear. Design: Integrative review. Data sources: Seven bibliographic databases (origin–2015), grey literature and reference lists were searched. Review methods: An integrative review method was used to synthesize data from diverse sources. Papers were selected through title and abstract screening and full‐text reviewing, using inclusion and exclusion criteria derived from review questions. Following quality appraisal, data were extracted and synthesized using normalization process theory as a framework. Results: The number of patients transferred home ranged from 1–346, with most papers reporting on the transfer of one or two patients. Four themes regarding transfer decision‐making work were generated: divergent views and practice, multiple stakeholders' involvement in decision‐making, collective work and limited understanding of individuals' experiences. Conclusion: The practice of transferring patients home to die and its decision‐making varies internationally and is usually influenced by the care system, culture or religion. It is less common to transfer patients home to die from critical care units in western societies. A better understanding of the decision‐making work was obtained but mainly from the perspective of hospital‐based healthcare professionals. Further research is needed to develop decision‐making practice guidance to facilitate patients' wishes to die at home.